The Natural History of Teneurins: A Billion Years of Evolution in Three Key Steps - Wides, Ron (Frontiers in Neuroscience, 2019)
The entire evolutionary history of the animal gene family, Teneurin, can be summed up in three key steps, plus three salient footnotes. In a shared ancestor of all bilaterians, the first step began with gene fusions that created a protein with an amino-terminal intracellular domain bridged via a single transmembrane helix to extracellular EGF-like domains. This first step was completed with a further gene fusion: an additional carboxy-terminal stretch of about 2000 amino acids (aa) was adopted, as-a-whole, from bacteria. The 2000 aa structure in Teneurin was recently solved in three dimensions. The 2000 aa region appears in a number of bacteria, yet was co-opted solely into Teneurin, and into no other eukaryotic proteins. Outside of bilaterian animals, no Teneurins exist, with a “Monosiga brevicollis caveat” brought below, as ‘the third footnote”. Subsequent to the “urTeneurin’s” genesis-by-fusions, all bilaterians bore a single Teneurin gene, always encoding an extraordinarily conserved Type II transmembrane protein with invariant domain content and order. The second key step was a duplication that led to an exception to singleton Teneurin genomes. A pair of Teneurin paralogs, Ten-a and Ten-m, are found in representatives all four Arthropod sub-phyla, in: insects, crustaceans, myriapods, and chelicerates. In contrast, in every other protostome species’ genome, including those of all non-Arthropod ecdysozoan phyla, only a single Teneurin gene occurs. The closest, sister, phylum of arthropods, the Onychophorans (velvet worms), bear a singleton Teneurin. Ten-a and Ten-m therefore arose from a duplication in an urArthropod only after Arthropods split from Onychophorans, but before the splits that led to the four Arthropod sub-phyla. The third key step was a quadruplication of Teneurins at the root of vertebrate radiation. Four Teneurin paralogs (Teneurins 1 through 4) arose first by a duplication of a single chordate gene likely leading to one 1/4–type gene, and one 2/3-type gene: the two copies found in extant jawless vertebrates. Relatively soon thereafter, a second duplication round yielded the 1 through 4 paralog types now found in all jawed vertebrates, from sharks to humans. It is possible to assert that these duplication events correlate well to the Ohno 2R hypothesis.